GRAVITY VARIATIONS AND RECENT GEODYNAMICS OF THE SOUTH-WESTERN PART OF THE BAIKAL REGION - V. Yu. Timofeev; Ye. N. Kalish; Yu. F. Stus'; D. G. Ardyukov; G. P. Arnautov; M. G. Smirnov; A. V. Timofeev; D. A. Nosov; I. S. Sizikov; E. V. Boiko; E. I. Gribanova (Геодинамика и тектонофизика, 2015)
Modern methods for determination of gravity values make it possible to obtain measurements with the accuracy up to 10–9 from g0 of the normal value (up to 1 microgal = 10 m/sec2). While all the systematic and periodic effects are excluded, a question is raised about stability of the gravity field of the Earth over time. Changes of the altitude (the Earth’s radius) with time can be estimated with an accuracy of 0.1 mm by modern space geodetic techniques, such as VLBI method. Our experiments for evaluation of stability of the gravity values over the past decades are based on the data obtained by Russian and foreign observatories using absolute ballistic laser gravimeters. The results put a limit of 10–10 per year to changes of the Earth’s radius. These estimations can be useful for testing hypotheses in tectonics.Measurements of non-tidal variations of gravity (Δg), which were obtained from 1992 to 2012 at the Talaya seismic station (located in the south-western part of the Baikal region), are interpreted together with GPS observation data. At the Talaya seismic station, the linear component of gravity variations corresponds to changes in the elevation of this site. The correlation coefficient is close to the normal value of the vertical gradient of gravity. At this site, coseismic gravity variations at the time of the Kultuk earthquake (27 August 2008, Mw=6.3) were caused by a combined effect of the change of the site’s elevation and deformation of the crust. Our estimations of the coseismic effects are consistent with results obtained by modeling based on the available seismic data.